Urban living labs : experimenting with city futures - Marvin, Simon, 1963-; Bulkeley, Harriet, 1972-; Mai, Lindsay; McCormick, Kes; Palgan, Yuliya Voytenko (London : Routledge, an imprint of the Taylor & Francis Group, 2018)
'The title examines, informs and advances the governance of sustainability transitions through urban living labs (ULL). ULL are increasing across the globe as a means by which actors are testing innovations in buildings, transport and energy systems. The book draws together researchers within a systematic comparative framework for evaluating the design, practices and processes of ULL to enable the analysis of their potential and limits. It provides new insights into the governance of urban sustainability and seeks to improve the design and implementation of ULL in order to realise their potential'--
Design of ULL -- Urban living labs : catalysing low carbon and sustainable cities in Europe? / Yuliya Voytenko Palgan, Kes Mccormick and James Evans -- Putting urban experiments into context : integrating urban living labs and city-regional priorities / Mike Hodson, James Evans and Gabriele Schliwa -- Urban living labs for the smart grid : experimentation, governmentality, and urban energy transitions / Anthony M. Levenda -- Smart city construction : towards an analytical framework for urban living labs -- Practices of ULL -- Intermediation and learning in Stellenbosch's urban living lab / Megan Davies and Mark Swilling -- Bringing urban living labs to communities : enabling processes of transformation / Janice Astbury and Harriet Bulkeley -- Homelabs : domestic living laboratories under conditions of austerity / Anna Davies -- Urban living labs,'smart' innovation and the realities of every day access to energy / Vanesa Cast Broto -- Processes of ULL -- 15-years and still living : the basel pilot region laboratory and Switzerland's pursuit of a 2000-watt society gregory trencher / Achim Geissler, Yasuhiro Yamanaka -- Agency, space, and partnerships : exploring key dimensions of urban living labs in Vancouver, Canada / Sarah Burch, Alex Graham and Carrie Mitchell -- Placing sustainability in communities : emerging urban living labs in China / Qianqing Mai -- The importance of place for urban transition experiments : understanding the embeddedness of urban living labs / Frank Van Steenbergen and Niki Frantzeskaki.
Includes bibliographical references and index.
Keywords: Sustainable urban development; City planning -- Environmental aspects; City planning -- Technological innovations; Urban ecology (Sociology)